Effectiveness of the use of implementation intentions on reduction of substance use: A meta-analysis. (1st September 2020) - Malaguti, Amy; Ciocanel, Oana; Sani, Fabio; Dillon, John F.; Eriksen, Ann; Power, Kevin
Highlights: Small significant effect of implementation intentions on reducing alcohol use, g = 0.31 (95 % CI: 0.21, 0.42), p < .001. Small significant effect of implementation intentions on reducing smoking behaviour, g = 0.31 (CI: 0.12, 0.5), p = .002. Lack of published research on the use of implementation intentions in populations who use illicit drugs. Abstract: Objective: Background : Substance use, such as alcohol drinking, tobacco smoking and illicit drug use, have been associated with severe health conditions and an annual estimated 12 % of all deaths worldwide. Implementation intentions are self-regulatory processes which help achieve health-related behaviour change. Objectives : To investigate the effectiveness of forming implementation intentions to reduce substance use. Design: Data sources : PsycINFO, MEDLINE, Psychology and Behavioural Science Collection, clinicaltrials.gov, UK Clinical Trials Gateway, Reference lists. Inclusion criteria : RCT of substance users forming implementation intentions to reduce consumption (active or passive control condition present). Study appraisal and synthesis methods : the SIGN checklist for RCT quality was used for quality appraisal, data was extracted by two reviewers. Results: Twenty-one studies were included in the meta-analysis. The overall effect size for alcohol use was g = 0.31 (95 % CI: 0.21, 0.42), p < .001; for tobacco smoking g = 0.31 (CI: 0.12, 0.5), p = .002; no studies were retrieved for the use of implementation intentions on illicit drug use. Conclusion: This review suggests that implementation intention interventions are effective in reducing some forms of substance use (alcohol use and tobacco smoking), albeit revealing small effect sizes, among the general population and students in secondary and higher education. Review registration number : CRD42018116170.